Răspunsuri

2014-08-27T12:16:01+03:00

4a² + 4b²= 14 ⇒⇒ a² + b²=14/4

I.  a² + b²= 4/4 + 10/4 = 1² + (√10/2)² ⇒ a= +1 sau - 1       b= +√10/2 sau  -√10/2            2a +2b - 7 =  2 + √10 - 7 = -5 + √10 sau  2 - √10 - 7 = -5 - √10 sau -2 + √10 - 7 =-9 + √10 sau -2 - √10 - 7 = -9-√10

II.  a² + b² = 9 /4 + 5/4 ⇒ a=3/2 sau -3/2   b=+√5/2 sau -√5/2  ⇒ 2a+2b - 7=3+√5-7=-4+√5 sau 3-√5 -7=-4-√5  sau -3+√5-7=-4+√5 sau -3-√5-7 =-10 -√5

daca enuntul e scris bine si nu mai sunt si alte conditii, se mai pot gasi si alte variante